Technology Transfer, Firm Ownership, and Investment in Human Capital - Ramachandran, Vijaya (The Review of Economics and Statistics, 1993)
Technology is transferred across countries at some cost to the transferor and transferee. Rather than treating transfer costs as determined by a Leontief type cost function, the author examines the incentive of each party to invest resources in transferring technology. The theoretical model predicts that subsidiaries will receive greater resources than partially licensor-owned and independent firms. The empirical analysis confirms this prediction. This result favors multinational investment over direct licensing of technology to independent firms. Copyright 1993 by MIT Press.